Nrf2 in Cancer, Detoxifying Enzymes and Cell Death Programs - Jenkins, Tabitha (Antioxidants (Basel), 2021)
Reactive oxygen species (ROS) play an important role in cell proliferation and differentiation. They are also by-products of aerobic living conditions. Their inherent reactivity poses a threat for all cellular components. Cells have, therefore, evolved complex pathways to sense and maintain the redox balance. Among them, Nrf2 (Nuclear factor erythroid 2-related factor 2) plays a crucial role: it is activated under oxidative conditions and is responsible for the expression of the detoxification machinery and antiapoptotic factors. It is, however, a double edge sword: whilst it prevents tumorigenesis in healthy cells, its constitutive activation in cancer promotes tumour growth and metastasis. In addition, recent data have highlighted the importance of Nrf2 in evading programmed cell death. In this review, we will focus on the activation of the Nrf2 pathway in the cytoplasm, the molecular basis underlying Nrf2 binding to the DNA, and the dysregulation of this pathway in cancer, before discussing how Nrf2 contributes to the prevention of apoptosis and ferroptosis in cancer and how it is likely to be linked to detoxifying enzymes containing selenium.